Toxicity of Bisphenol A in Rats: A Study of its Accumulation and Effects on Brain, Kidneys, Liver and Blood Serum - Abdulhasan, Zaid abdulhamza; Hussein, Haider Mashkoor (American Journal of Botany and Bioengineering, 2026)
This study investigates the harmful effects of Bisphenol A (BPA) bioaccumulation in the brain, liver, kidneys, and blood serum of albino rats. BPA, a chemical widely used in plastics and resins, is known to disrupt endocrine function and pose health risks. Twenty-four adult rats, including 12 males and 12 females, were divided into three groups, each receiving different doses of BPA over six weeks. BPA was administered orally with corn oil. Tissue samples from the brain, liver, kidneys, and serum were analyzed using High-Performance Liquid Chromatography (HPLC). Results showed a significant accumulation of BPA in the brain, liver, and kidneys, with higher concentrations observed compared to serum. The accumulation followed a dose-dependent pattern, with the highest BPA levels in the group receiving the maximum dose. Furthermore, differences in BPA accumulation were noted between males and females. The aim of this study is to understand the extent of BPA bioaccumulation in various organs and explore sex-specific variations in the effects of BPA exposure.